PERAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TERHADAP PENINGKATAN SUMBER DAYA MANUSIA DI KABUPATEN BARITO UTARA: - SOFIA (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2017)
In the era of regional autonomy where the system of deconcentration and decentralization is also the authority of the regions in regulating their own households, requires a qualified and highly motivated apparatus in facing global challenges in the future. Quality and professionalism within government organizations, underpinning the progress of leadership management so as to affect the improvement of quality and professionalism of human resources. This research is descriptive by using case method (case study) to the object of research where first conducted preliminary survey to know the general picture. The sample used comes from the population of Civil Servants (PNS) who have completed / followed the level IV training from 2007 - 2009 (3 years budget). The results showed that there is a positive role / relationship between Diklatpim Level IV with the quality improvement of Apparatus Resources which showed the correlation coefficient value (r) of 0.625 which means Interpretation of Correlation Coefficient is at the level of strong relationship. The roles / relationships occur significantly (significant) between Diklatpim Level IV to the quality improvement of Apparatus Resources indicated by the Thitung level of 4.2371. This means the value of Thitung> ttabel (4.2371> 0.361).